169k views
3 votes
Consider this system of linear equations:

22x − y = -23 (equation 1)

11x + 12y = 1 (equation 2)

2 Answers

2 votes
To solve this problem you must apply the proccedure shown below:

1. You have the folllowing system of equations given in the problem above:

22x − y = -23 (equation 1)
11x + 12y = 1 (equation 2)

2. If you multiply the equation 2 by -2, and then sum the equation 1+equation 2, you obtain:

-25y=-25
y=1

3. Then, you must substitute y=1 into the equation 1, then you have:

x=-1

4. As you can see, when you solve it, the solutions are:

x=-1
y=1
User Chet Meinzer
by
4.7k points
4 votes
Using subtraction method or elimination method

22x − y = -23
-
(11x + 12y = 1) *2

22x − y = -23
-
22x + 24y = 2
0 -25y = -25
y = 1

22x - 1 = -23
x = 1


User Fesja
by
4.9k points